IDENTIFIKASI SERANGAN HAMA KUTU PUTIH (Pseudococcus citri) PADA BUAH KAKAO (Theobroma cacao L.) DAN UPAYA MENEKAN SERANGAN DENGAN CENDAWAN Beauveria bassiana - Iin Arsensi; Yohanes Yanuarius Hang; Rustam Baraq Noor (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
The purpose of this study was to determine the population of mealybugs before and after application of the fungus Beauveria bassiana, to determine the mortality of mealybugs after application of the fungus Beauveria bassiana, and to determine the appropriate dose of the fungus Beauveria bassiana to control mealybugs. This research was conducted from early April to July 2021 and took place in the community garden in Teluk Kedondong Village, RT 22, Sempaja Utara Village, North Samarinda District. The study used purposive sampling method with 4 doses of Beauveria bassiana repeated 5 times (B0 = Control), (B1 = 5 g/ Liter of water), (B2 = 10 g/ Liter of water), (B3 = 15 g/ Liter of water). ). Based on the results of the study, the identification of the attack rate of mealybugs (Pseudococcus citri) on cocoa (Theobroma cacao L.) and efforts to suppress its attack with the fungus Beauveria bassiana, it can be concluded that: After application of the fungus Beauveria bassiana the population of mealybugs showed a decrease. The mortality of mealybugs after application of the fungus Beauveria bassiana was 100%. The best and most effective dose in suppressing the attack of mealybugs is 5 g/liter of water. To suppress the attack of mealybugs, it is recommended to use a dose of 5 g/liter of water by spraying it on the fruit and then wrapping it in plastic so that the fungus can be more effective.